A Method of Identifying the Characteristic Parameter of Material by Using Modal Test and Finite Element Analysis - Wang Lixin; Chen Linkai (Jixie chuandong)
Taking the front housing of a certain type of planetary gearbox as the research object. At first,by using the LMS modal test system,an impact hammer test on the front housing of gearbox is performed,which is hung with rubber bands to simulate the free boundary conditions. By processing the collected data with LMS Test. Lab software,the first 8 order natural frequencies and damping ratios of the front housing of gearbox are identified. The modal results are verified according to the modal confidence criterion,it turns out that the experimental modal parameters identification results are reliable. Since the specific materials and grades of the cabinet are unknown,the accurate finite element model can’t be established. Combining numerical simulation with experimentation,the experimental parameter set is established by using the multi-factor orthogonal test method,and finally the reliable material property parameters of the gearbox are obtained.